The Untapped Australasian Diversity of Astaxanthin-Producing Yeasts with Biotechnological Potential—Phaffia australis sp. nov. and Phaffia tasmanica sp. nov. - Márcia David-Palma; Diego Libkind; Patrícia H. Brito; Margarida Silva; Nicolás Bellora; Marco A. Coelho; Joseph Heitman; Paula Gonçalves; José Paulo Sampaio (Microorganisms, 2020)
Phaffia is an orange-colored basidiomycetous yeast genus of the order Cystofilobasidiales that contains a single species, P. rhodozyma. This species is the only fungus known to produce the economically relevant carotenoid astaxanthin. Although Phaffia was originally found in the Northern hemisphere, its diversity in the southern part of the globe has been shown to be much greater. Here we analyze the genomes of two Australasian lineages that are markedly distinct from P. rhodozyma. The two divergent lineages were investigated within a comprehensive phylogenomic study of representatives of the Cystofilobasidiales that supported the recognition of two novel Phaffia species, for which we propose the names of P. australis sp. nov. and P. tasmanica sp. nov. Comparative genomics and other analyses confirmed that the two new species have the typical Phaffia hallmark—the six genes necessary for the biosynthesis of astaxanthin could be retrieved from the draft genome sequences, and this carotenoid was detected in culture extracts. In addition, the organization of the mating-type (MAT) loci is similar to that of P. rhodozyma, with synteny throughout most regions. Moreover, cases of trans-specific polymorphism involving pheromone receptor genes and pheromone precursor proteins in the three Phaffia species, together with their shared homothallism, provide additional support for their classification in a single genus.